The Nature of the Relationship Between Corporate Identity and Corporate Sustainability: Evidence from The Retail Industry. Issue 3 (19th June 2017) - Simões, Cláudia; Sebastiani, Roberta
ABSTRACT: This article addresses the nature of the interface between corporate sustainability and corporate identity at both the strategic and instrumental levels. We developed an empirical qualitative study in two countries in Southern Europe addressing retailers who are actively engaged in pursuing corporate-sustainability strategies. Data sources include in-depth interviews, observations, and physical artifacts of identity (digital and printed documents). Findings reveal that, at a strategic level, corporate sustainability is embedded in corporate identity reflecting the company's strategy. Companies also instrumentally use corporate identity to operationalize corporate sustainability strategies. Organizations show different patterns in the way they bridge corporate sustainability and identity. The contributions of this article are threefold: it reports the symbiotic relationship between corporate sustainability and corporate identity; it scrutinizes how corporate sustainability and corporate identity are integrated at the strategic and operational levels; and it establishes distinct patterns at the interface of corporate sustainability and corporate identity.